Delusional and psychotic disorders in juvenile myotonic dystrophy type‐1. Issue 4 (27th April 2017) - Jacobs, Delphine; Willekens, Diane; de Die‐Smulders, Christine; Frijns, Jean‐Pierre; Steyaert, Jean
Abstract : We investigated the clinically derived hypothesis of a relatively high incidence of delusional and psychotic disorders in adolescents with juvenile Myotonic Dystrophy type‐1 (DM1). Twenty‐seven subjects of age 16–25 with juvenile DM1 and their parents were invited to have a clinical psychiatric interview, and to complete an ASEBA behavior checklist (YSR, ASR, CBCL, and ABCL). We diagnosed a Delusional Disorder in 19% of our patients and a Psychotic Disorder not otherwise specified in another 19%. These two groups of patients had a significantly worse level of clinically defined general functioning. It is clinically relevant to investigate in patients with juvenile DM the symptom of delusions and the presence of a delusional and psychotic disorder, and to consider the presence of juvenile DM in youngsters presenting with such a thought disorder. These disorders compromise the general functioning of the subjects and are often to some extent treatable. © 2017 Wiley Periodicals, Inc.